EFEKTIVITAS TERAPI FOOT MASSAGE TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DI WILAYAH KERJA PUSKESMAS PAMPANG - Della Adelia Panggiling; Akbar Asfar; Brajakson Siokal; Suci Hardiyanti Suharto Putri (Jurnal Kesehatan, 2025)
Hypertension is a non-communicable disease with a high prevalence and is known as a silent killer because it can cause serious complications without clear early symptoms. Hypertension management is generally carried out with pharmacological therapy, but non-pharmacological therapies such as foot massage have also been proven effective. Foot massage is a technique that provides relaxation, improves blood circulation, and reduces sympathetic activity, thus lowering blood pressure. This study aims to determine the effectiveness of foot massage in reducing blood pressure among hypertensive patients. The benefits of this study are expected to provide input for students, educational institutions, healthcare providers, and patients with their families as a complementary alternative therapy. The method used was a case study on a patient with hypertension in the working area of Pampang Health Center, with a 20-minute foot massage intervention. The results showed a significant decrease in blood pressure from 180/97 mmHg to 173/90 mmHg on the first day, and from 169/90 mmHg to 158/87 mmHg on the second day. The patient also reported a reduction in pain scale from 4 to 3 and felt more relaxed. In conclusion, foot massage is an effective, safe, and low-cost complementary therapy for hypertension control